Firm Leverage, Consumer Demand, and Employment Losses During the Great Recession* - Giroud, Xavier; Mueller, Holger M. (Quarterly Journal of Economics, 2017)
Abstract This article argues that firms’ balance sheets were instrumental in the transmission of consumer demand shocks during the Great Recession. Using micro-level data from the U.S. Census Bureau, we find that establishments of more highly levered firms experienced significantly larger employment losses in response to declines in local consumer demand. These results are not driven by firms being less productive, having expanded too much prior to the Great Recession, or being generally more sensitive to fluctuations in either aggregate employment or house prices. Likewise, at the county level, we find that counties with more highly levered firms experienced significantly larger declines in employment in response to local consumer demand shocks. Accordingly, firms’ balance sheets also matter for aggregate employment. Our results suggest a possible role for employment policies that target firms directly besides conventional stimulus.